CHEMICAL SOIL ATTRIBUTES IN DIFFERENT USE SYSTEMS, ITACOATIARA-AM, BRAZIL - VILLACIS-FAJARDO, Juan Daniel (2021)
The use of soil to implement several management systems, such as agriculture, livestock farming and agroforestry activities contribute to the depletion of the soil and the forest, reducing or increasing the levels of soil chemical attributes, such as calcium, magnesium, potassium, and phosphorus and increase or decrease of active (pH) or exchangeable (Aluminum) acidity. This study aimed to evaluate macronutrients (calcium - Ca2+, magnesium - Mg2+, potassium - K+ and phosphorus - P), as well as aluminum - Al3+ and soil pH, under use systems: agroforestry system - SAFs and pasture - PA, comparing them to Primary Forest - PF, in the Rosenthal community in Itacoatiara-AM, Brazil. The soils were sampled in layers 0-10 cm and 10-20 cm deep, with samples composed of six single samples each. The distribution of nutrient contents (Ca2+, Mg2+, K+ , and P) considering the 0-10 and 10-20 cm layers showed little variation, except for phosphorus, which obtained the highest concentration in the prospected layers. The distribution of calcium, magnesium, and potassium nutrients in the sampled soil layers decreased with depth. However, an inverse pattern was observed in the elevation of active soil acidity and aluminium levels. Soil macronutrients showed medium to high concentrations, with forest and SAFs as systems that preserve good levels of fertility.